Evaluation of Potential Antihypertensive Drug Interactions in Hospitalized Patients: A Retrospective Study Based on Medical Records - Annora rizky amalia; Alfina Nurrahman; Bella Anggreyani Yusuf (Jurnal Surya Medika (JSM), 2026)
Hypertension is a chronic disease that requires long-term treatment. The concomitant use of multiple medications in hospitalized patients may increase the risk of potential drug interactions, which can affect treatment effectiveness and patient safety. This study aimed to evaluate potential antihypertensive drug interactions in hospitalized patients based on medical record data. A descriptive study with a retrospective design was conducted by reviewing the medical records of patients with hypertension at a regional public hospital in Central Java. The samples were selected using purposive sampling according to the predetermined inclusion and exclusion criteria. Potential drug interactions were analyzed based on the combinations of medications prescribed during hospitalization. The results showed that 85 patients (70.83%) had potential drug interactions, with a total of 208 interaction events, of which 155 (74.52%) involved antihypertensive drugs. The most frequent potential interaction occurred between amlodipine and Santagesik, accounting for 20 events (9.62%). Most interactions were classified as significant (77.40%) and were predominantly pharmacokinetic in mechanism (79.81%). Potential antihypertensive drug interactions remain common among hospitalized patients, highlighting the importance of regular therapy evaluation and medication monitoring to improve treatment safety and effectiveness.